Autophagy-related gene 5 (Atg5) is required for maintaining subcellular calcium homeostasis during acute cardiac stress. (14th October 2021) - Djalinac, N; Voglhuber, J; Ljubojevic-Holzer, S; Sedej, S
Abstract: Background: Autophagy exerts protective effects during cardiac stress inflicted by β-adrenergic stimulation and pressure overload. Contrarily, deletion of the cardiac-specific Atg5 gene contributes to left ventricular hypertrophy and contractile dysfunction, resulting in dilated cardiomyopathy. Heart failure is characterized by perturbations of excitation-contraction coupling (ECC) underlying alterations in intracellular calcium signaling. Purpose: In this study, we aimed to understand whether loss of basal autophagy due to Atg5 deletion specifically in cardiomyocytes contributes directly to disturbances in subcellular calcium cycling. Methods: Cardiac-specific Atg5−/− and Atg5+/+ mice were used to isolate ventricular cardiomyocytes, which were loaded with 8 μM Ca2+ indicator Fluo4/AM. Isolated cells were electrically stimulated and subjected to elevated workload by increasing pacing frequencies from 1 to 4 Hz. Cytosolic and nuclear calcium transients (CaTs) were recorded in line-scan mode using a laser scanning confocal microscope. Pharmacological inhibition of autophagic flux was performed by an intraperitoneal injection of 40 mg/kg leupeptin to Atg5+/+ mice. Results: At baseline (1 Hz) stimulation the amplitude and kinetics of calcium transients were comparable between Atg5−/− and Atg5+/+ cells. However, after progressive increase of the pacing rate from 1 Hz to 4 Hz, Atg5−/− cardiomyocytes displayed reduced cytoplasmic and nuclear CaT amplitude, but increased nuclear time-averaged CaTs compared to controls. Such increase in nuclear calcium load stimulates Ca2+-dependent transcriptional activity, and likely involves CaMKII-mediated pro-hypertrophic gene program thus contributing to cardiac remodelling. In addition, we observed increased occurrence of arrhythmic events in Atg5−/− hearts at high pacing frequency, indicative of intracellular calcium overload and disturbed ECC. Acute pharmacological autophagy inhibition failed to elicit direct changes in time-averaged CaTs in the cytoplasm and nucleoplasm, suggesting that loss of Atg5-dependent autophagy seems to induce adverse cardiac remodelling that involves increased CaMKII activity due to the imbalances in nuclear Ca2+ levels. Conclusion: Specific loss of ATG5 protein impairs calcium cycling during acute stress exposure by reducing CaT amplitudes, promoting arrhythmia, and increasing nuclear calcium load, which may induce hypertrophic gene expression. Further work is needed to identify key components mediating autophagy-related cardioprotection to develop strategies against cardiac remodeling and its progression to heart failure. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Austrian Science Fund (FWF)